The Mediating Role of Work Engagement Between the Influence of Learning Culture on the Learning Agility of Millennial Employees - Benedikta Gaudensia Sura; Reny Yuniasanti; Nina Fitriana (ANFUSINA: Journal of Psychology, 2025)
The study examines how learning culture affects learning agility among millennial employees at Company "X," with work engagement as a mediator with Affective Event Theory (AET). Millennials, being adaptive to communication, media, and digital technology, are advantageous for companies in a VUCA (volatility, uncertainty, complexity, and ambiguity) environment. The purpose of this study is to examine the indirect effect of learning culture on learning agility with work engagement as a mediator variable. This quantitative research involved 156 millennial employees from purposive sampling with aged 23-44 years, who have worked at the company for at least three months. Data were collected using the Burke Learning Agility Inventory (BLAI), Organization Learning Culture (OLC), and the 9-item version of the Utrecht Work Engagement Scale (UWES). The analysis used PLS-SEM and the results showed path coefficient is 0.502 (the p-values 0.000,  p value < 0.05) and a positive t-value of 8.580 (t-value >1.96).  It can be stated that work engagement mediates the influence of learning culture on the learning agility of millennial employees at Company “X. Through this research, it is hoped that it can provide manajemen information to design intervention for companies in enhancing learning culture in organization to show work enggagement and increase  learning agility of millennial employees in the company. Keywoards: Learning Agility, Learning Culture, Work Engagement, Millennial Generation